Risk and prognostic factors for severe leptospirosis in adult population in intensive care unit Hospital Perempuan Zainab II, Kota Bharu - Yen, Yew Chee (2017)
Background: Leptospirosis has a wide range of clinical presentation from mild to severe disease with organ dysfunctions and death. There are risk and prognostic factors for severity and mortality including demographic, epidemiological, clinical presentations and laboratory results. Early recognition of risk factors enables early ICU care and organ supports. Purpose: The study was conducted to identify the risk and prognostic factors for severe leptospirosis and its mortality. Methods: This was a retrospective case-control study carried out in the general ICU in Hospital Raja Perempuan Zainab II from 1st January 2013 to 31st December 2016. Patients who presented with severe organ involvement which required dialysis, tracheal intubation and mechanical ventilation, vasopressors or inotropes, transfusion or death were grouped as cases. Controls were defined as patient with mild organ involvement without requirement or with minimal organ supports. Chi-Square test, Fisher‘s exact test, Student t-test or Mann Whitney test was used. A logistic regression model was used to select final prognostic factors. Results: Ninety six leptospirosis patients were included in the study. Among 96 patients enrolled in the study, 66 patients were in the severe group, 30 patients were in the control group. Seven risk factors independently associated with severe leptospirosis: Aspartate Transferase (AST) (OR: 4.2 [1.608, 10.970], P=0.002); Alanine Transferase (ALT) (OR:2.857 [1.153, 7.082], P=0.021); Urea (OR:2.895 [1.081,7.753], P=0.031); Prothrombin time (PT) (OR:4.797 [1.629,14.126], P=0.003); International Normalised Ratio (INR) (OR: 3.714[1.157, 11.920], P=0.021); Ratio (OR: 8.399); Creatine kinase MB (CKMB) (OR:7.0 [1.961,24.985], P=0.001). Six independent risk factors were associated with mortality: Simplified Acute Physiology Score II (SAPS II) score (OR: 1.045 [1.007-1.083], P=0.019); PT (1.069 [0.00--], P=0.038); INR (OR: 4.48 [1.524-13.17], P=0.005), Activated partial thromboplastin time (APTT) (OR:2.933 [0.993-8.66], P=0.048), ratio (OR:21.87[2.52-189.86], P=0.001), Electrocardiography (ECG) (OR1.13 [0.00--], P=0.048) Conclusion: Leptospirosis patients with elevated liver enzymes, elevated urea, coagulopathy and elevated CKMB were risky to develop severe leptospirosis. SAPS II, coagulopathy and ECG changes were high risk for mortality.